Low-Dose Imaging in a New Preclinical Total-Body PET/CT Scanner - Molinos, Cesar; Sasser, Todd; Salmon, Phil; Gsell, Willy; Viertl, David; Massey, James C.; Mińczuk, Krzysztof; Li, Jie; Kundu, Bijoy K.; Berr, Stuart; Correcher, Carlos; Bahadur, Ali; et al. (Frontiers in Medicine, 2019)
Ionizing radiation constitutes a health risk to imaging scientists and study animals. Both PET and CT produce ionizing radiation. CT doses in pre-clinical in vivo imaging typically range from 50 to 1000 mGy and biological effects in mice at this dose range have been previously described. [18F]FDG body doses in mice have been estimated to be in the range of 100 mGy for [18F]FDG. Yearly, the average whole body doses due to handling of activity by PET technologists are reported to be 3 to 8 mSv. A preclinical PET/CT system was designed for low-dose PET and CT capabilities suitable for small animal studies. The CT subsystem uses a X-source power that is optimized for small animal imaging. The system design incorporates a spatial beam shaper coupled with a highly sensitive flat-panel detector and very fast acquisition (< 10 s) which allows for whole body scans with doses as low as 6 mGy. The mouse total-body PET subsystem uses a detector architecture based on continuous crystals, coupled to SiPM arrays and a readout based in rows and columns. The PET field of view is 150 mm axial and 80 mm transaxial. The high solid-angle coverage of the sample and the use of continuous crystals achieve a sensitivity of 9% (NEMA) that can be leveraged for use of low tracer doses and/or performing rapid scans. The low-dose imaging capabilities of the total-body PET subsystem were tested with NEMA phantoms, in a breast cancer model, a mouse bone metabolism scan and a rat heart dynamic scan. The CT imaging capabilities were tested in mice and in a low contrast phantom. The PET low-dose phantom and animal experiments provide evidence that image quality suitable for preclinical PET studies is achieved. Furthermore, CT image contrast using low dose scan settings was suitable as a reference for PET scans. Total-body mouse PET/CT studies could be completed with total doses of <10 mGy.